2008
DOI: 10.1038/nature07060
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial progenitors contribute to the cardiomyocyte lineage in the developing heart

Abstract: The heart is formed from cardiogenic progenitors expressing the transcription factors Nkx2-5 and Isl1 (refs 1 and 2). These multipotent progenitors give rise to cardiomyocyte, smooth muscle and endothelial cells, the major lineages of the mature heart. Here we identify a novel cardiogenic precursor marked by expression of the transcription factor Wt1 and located within the epicardium-an epithelial sheet overlying the heart. During normal murine heart development, a subset of these Wt1(+) precursors differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

41
1,013
3
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 923 publications
(1,068 citation statements)
references
References 35 publications
41
1,013
3
11
Order By: Relevance
“…This correlates with ''late'' effects of RA in regulating myocardial compact zone growth by inducing growth factor signaling and/or cardiomyocyte differentiation (Merki et al, 2005;Lin et al, 2010), and potentially in regulating the epicardial to myocardial lineage conversion (Cai et al, 2008;Zhou et al, 2008). It is noteworthy that a large part of the myocardium (i.e.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This correlates with ''late'' effects of RA in regulating myocardial compact zone growth by inducing growth factor signaling and/or cardiomyocyte differentiation (Merki et al, 2005;Lin et al, 2010), and potentially in regulating the epicardial to myocardial lineage conversion (Cai et al, 2008;Zhou et al, 2008). It is noteworthy that a large part of the myocardium (i.e.…”
Section: Discussionmentioning
confidence: 80%
“…These include (i) the ''first heart field'' or cardiac crescent formed from mesoderm emerging from the primitive streak (Garcia-Martinez and Schoenwolf, 1993;Tam et al, 1997); (ii) the ''second heart field'' originating from pharyngeal mesoderm (Buckingham et al, 2005); (iii) the (pro)epicardium, a population originating and giving rise to coronary vasculature, myocardial fibroblasts and to a distinct cardiomyocytic lineage (Cai et al, 2008;Zhou et al, 2008), and (iv) the ''cardiac'' neural crest, a subset of post-otic neural crest cells migrating through the third to sixth branchial arches and participating to the development of the aortic arches and aorticopulmonary septum (reviewed by Rochais et al, 2009). All these lineages have been reported to be influenced by embryonic RA (Hochgreb et al, 2003;Ryckebusch et al, 2008;Sirbu et al, 2008;Dupe and Pellerin, 2009), although recent studies implicate the second heart field (Ryckebusch et al, 2008;Sirbu et al, 2008) and the epicardium (Merki et al, 2005;Lin et al, 2010) as the main sites of RA signaling.…”
Section: Branchial Arches and Heartmentioning
confidence: 99%
“…The epicardium has been reported to play an active role during normal cardiomyogenesis 25, while it becomes quiescent after birth 26. Although the mammalian epicardium is activated after MI, the number of the activated cells is insufficient for myocardium repair 27, 28.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart and gut, lineage-tracing of the outer mesothelial layer, using mesothelial-specific Wt1-Cre mouse strains, has shown that the mesothelium is the source of $80% of the vascular smooth muscle cells during embryonic development (Wilm et al, 2005;Zhou et al, 2008). Similar A: Hematoxylin and eosin stained section of an embryonic day (E) 12.5 left lung lobe.…”
Section: Vascular Smooth Muscle Progenitorsmentioning
confidence: 99%